a Analisa Studi Kelayakan Happiness Café Berdasarkan Aspek Keuangan: Analysis of the Feasibility Study of the Happiness Café in terms of Financial Aspects - Iskandar, Ridwan; Tarin, Hillary (JURNAL BISNIS HOSPITALITI, 2025)
Abstract The culinary business is one of the businesses that has developed rapidly recently. Today's society tends to be busy and highly mobile. People nowadays spend more time outside the home. According to the business environment analysis that has been carried out, the people of Cibubur Tourism City tend to have high mobility and spend a lot of time outside the home and prefer to eat and drink outside the home for fast and practical reasons. After discovering the problem that Indonesia is the largest cocoa producer, but more of it is exported to foreign countries, I plan to build a new business in the form of chocolate cafes with the name Happiness Cafe. In order to find out the business opportunities, the following is a calculation that will determine the feasibility of this chocolate cafe business. Eligibility criteria analysis produces a Payback Period (PP) of 2 years 2 months, Average Rate of Return (ARR) of 56%, Net Present Value (NPV) of Rp 44.493.995, Internal Rate of Return (IRR) of 34% and  Profitability Index (PI) of 1,4.